A Programmable Dual‐Regime Spray for Large‐Scale and Custom‐Designed Electronic Textiles. Issue 9 (24th January 2022) - Chang, Taehoo; Akin, Semih; Kim, Min Ku; Murray, Laura; Kim, Bongjoong; Cho, Seungse; Huh, Sena; Teke, Sengul; Couetil, Laurent; Jun, Martin Byung‐Guk; Lee, Chi Hwan
Abstract: Increasing demand for wearable healthcare synergistically advances the field of electronic textiles, or e‐textiles, allowing for ambulatory monitoring of vital health signals. Despite great promise, the pragmatic deployment of e‐textiles in clinical practice remains challenged due to the lack of a method in producing custom‐designed e‐textiles at high spatial resolution across a large area. To this end, a programmable dual‐regime spray that enables the direct custom writing of functional nanoparticles into arbitrary fabrics at sub‐millimeter resolution over meter scale is employed. The resulting e‐textiles retain the intrinsic fabric properties in terms of mechanical flexibility, water‐vapor permeability, and comfort against multiple uses and laundry cycles. The e‐textiles tightly fit various body sizes and shapes to support the high‐fidelity recording of physiological and electrophysiological signals on the skin under ambulatory conditions. Pilot field tests in a remote health‐monitoring setting with a large animal, such as a horse, demonstrate the scalability and utility of the e‐textiles beyond conventional devices. This approach will be suitable for the rapid prototyping of custom e‐textiles tailored to meet various clinical needs. Abstract : A programmable dual‐regime spray that enables direct writing of custom electronic textiles (e‐textiles) into stretch fabrics or garments over meter scale is introduced. The e‐textiles tightly fit various body sizes and shapes of large animals to support reliable monitoring of health data under ambulatory conditions in a wirelessly controlled fashion.